1976
DOI: 10.1073/pnas.73.3.857
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism for translational control in regulation of ferritin synthesis by iron.

Abstract: Poly(A)containing RNA was isolated from the polyribosomal and post-ribosomal fractions of the livers of normal and iron-treated rats. These RNA fractions were then translated in a wheat germ system to provide a measure of the amount of ferritin mRNA present in each fraction. Following iron administration, there was a 2-fold increase in the amount of ferritin mRNA in the polyribosomal fraction. This increase was not inhibited by prior treatment of the rats with actinomycin D or cordycepin, suggesting a cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
135
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(141 citation statements)
references
References 45 publications
6
135
0
Order By: Relevance
“…This is supported by the observation that SF levels are raised during both mild and severe infections, similar to earlier observations (Konijn et al, 1981). Zahringer et al (1976) reported an increase in synthesis of apoferritin by the membrane-bound polysomes with subsequent release into circulation as an acute phase response to infection. Being apoferritin in nature, SF fails to reflect the true iron status of the individual and thus has limited use as a marker of iron status during infection.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by the observation that SF levels are raised during both mild and severe infections, similar to earlier observations (Konijn et al, 1981). Zahringer et al (1976) reported an increase in synthesis of apoferritin by the membrane-bound polysomes with subsequent release into circulation as an acute phase response to infection. Being apoferritin in nature, SF fails to reflect the true iron status of the individual and thus has limited use as a marker of iron status during infection.…”
Section: Discussionsupporting
confidence: 89%
“…The yohimbine effect, therefore, is more than simply displacing the IRP. One explanation could be that unwinding of the IRE structure by yohimbine is more complete than by endogenous initiation factors, a conjecture supported by the observations that during iron overload, when the IRP is presumed to be displaced (51), 40 -50% of endogenous ferritin mRNA remains untranslated (52,53). The complexity of the interactions among the IRE RNA, IRP repressor, and initiation factor proteins is illustrated by the binding of the IRP repressor to both the IRE and the large initiation scaffold protein, eIF-4G (54).…”
Section: Discussionmentioning
confidence: 89%
“…4B) shows Fe 2þ metabolite-regulated IRE-mRNA-IRP inhibition of protein synthesis, where ribosome binding is prevented (7,15,28), combined with Fe 2þ -metabolite regulated IRE-mRNA-eIF4F enhancement of protein synthesis (Fig. 4A), where ribosome binding is facilitated.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the 30 nt IRE-RNA not only removes IRP regulation but also decreases the rate of IRP-independent protein synthesis (14). A number of current models of IRE-RNA/IRP regulation feature iron-dependent degradation/modification of the IRP proteins as the main control point (8,9,15,16). Such models do not answer two important questions: (i) How does iron increase release of IRP protein for [4Fe-4S]-modification and/or degradation?…”
mentioning
confidence: 99%